A Quantum Public-Key Cryptosystem Without Quantum Storage for Public-Keys - Li, Xiaoyu; Fang, Zhipeng (Contemporary Mathematics, 2025)
A quantum public-key cryptosystem without quantum storage for public-keys is provided. In traditional quantum public-key cryptosystems the public key of a user is a set of quantum systems. There is a Key Management Center (KMC) which needs to keep the public keys of all users for a long time to satisfy communication requirements between users. But it’s very difficult to keep quantum systems for a long time because quantum system will undergo decoherence with time. This is a big obstacle for quantum public-key cryptosystems when they are applied in practice. This quantum public-key cryptosystem can solve this problem. A user keeps a state sequence and a binary string in the key management center called the source key which is only a piece of classical information. If one user A wants to have another user B to get a secret message, KMC creates a sequence of quantum systems according to the latter one’s source key, which is just the user’s (public key, private key) pair. Then the two users can accomplish secure communications with KMC’s assistance. On the otherhand users can also perform message authentication on the messages to guarantee that the messages can’t be forged or distorted. In this cryptosystem KMC needs no quantum storage for public keys, which greatly reduces the technical difficulties of key management and secret communication. Moreover any two users needn’t keep a quantum channel between them. Therefore to realize and apply this quantum public-key cryptosystem is much more easier than traditional quantum public-key cryptosystems.